Pengaruh Pemberian Tepung Daun Kelor Untuk Mencegah Anemia Pada Remaja Wanita : Systematic Literature Review - Selvia, Dina; Andini, Neng Diana Putri; Rofifah, Khairunnisa Nabilatun; Zahra, Siti Fatimah; Putri, Imbaraniati Permana; Anjani, Sri Ulan; Ridwan, Heri Ulan; Setiadi, Diding Kelana (Jurnal Ilmiah Wahana Pendidikan, 2024)
Anemia is when the body lacks healthy red blood cells or hemoglobin, resulting in reduced oxygen supply to tissues and organs. This disease generally occurs in adolescents, especially adolescent girls. This is because young women experience menstrual periods and do not get enough iron, therefore anemia is a health problem that is often found throughout the world. The Moringa leaf plant (Moringa oleifera) is believed to contain iron which can help increase hemoglobin levels in the body. This study aims to determine the effectiveness of Moringa Oleifera leaf flour to prevent iron deficiency anemia in female adolescents. The research uses a literature review study approach, namely by searching for literature material regarding themes that will be taken in identifying national and international literature using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology through four stages: identification, screening, eligibility, and acceptable outcomes. This literature search was carried out by accessing online electronic databases from Cochrane and Google Scholar. Of the 4,392 articles searched, there were 8 articles and journals that met the desired criteria with the results proving that Moringa leaf powder contained 28.2 milligrams/100 grams so it was more effective in increasing hemoglobin levels. Moringa leaf flour has proven to be very effective in increasing hemoglobin in the body, especially for young women, so it can prevent anemia.